PEMBERIAN KOMBINASI PUPUK KANDANG DENGAN TRICHO-KOMPOS TERHADAP PERTUMBUHAN TANAMAN SORGUM (Sorghum bicolor. L) - Puspita, Fifi; Yoseva, Sri; ', Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Sorghum is one of the agricultural that commodities that have known for a long time in indonesia. The study was conducted to determine the affect and get the best combination of manure Tricho-kompos on the growth of sorghum (sorghum bicolor. L). The research was carried out on the ground field PMK in field trials with pH 4,5 which is in the Pangkalan Baru village, subdistrict Siak Hulu, Kampar district. This research was carried out for 4 months starting in January 2014 until April 2014 that cooperated with LIPI. The experimental design used was a randomized complete block design consisting of 3 treatments and 6 groups, in order to obtain 18 units of trial. The first treatment is the provision of chicken manure, the second treatment is a combination of chicken manure with Tricho-kompos and the second treatment is a combination of goat manure with Tricho-kompos, with a spacing of 11 m x 5,5 m. The combination of chicken manure with Tricho-kompos showed the best results compared with a combination of goat manure with Tricho-kompos and only chicken manure. Keyword: Manure, Sorghum varieties CTY33, Tricho-kompos